Influence of Androgen Deprivation Therapy on the PD-L1 Expression and Immune Activity in Prostate Cancer Tissue - Sommer, Ulrich; Ebersbach, Celina; Beier, Alicia-Marie K.; Baretton, Gustavo B.; Thomas, Christian; Borkowetz, Angelika; Erb, Holger H. H. (Frontiers in Molecular Biosciences, 2022)
Immune checkpoint inhibitors have become a promising new therapy for cancer treatment. However, due to prostate cancer’s high heterogeneity and immune-suppressive tumour microenvironment, clinical trials with immune checkpoint inhibitors for prostate cancer resulted in low or no response. This descriptive and retrospective study investigates the influence of ADT on PD-L1 expression and CD8+ T-cell tumour infiltration and activity in primary prostate cancer tissue. Therefore, immunohistochemistry was used to assess PD-L1, CD8+ T-cell, and the immune activation marker Granzyme B (GrB) in PCa tissue before and under ADT. In line with previous studies, few prostate cancer tissues showed PD-L1 expression and CD8+ T-cell infiltration. However, PD-L1 expression levels on tumour cells or infiltrating immune cells above 5% generated an immune-suppressive tumour microenvironment harbouring hypofunctional CD8+ T-cells. Moreover, analysis of a longitudinal patient cohort before and under ADT revealed that ADT increased hypofunctional CD8+ T cells in the tumour area suggesting a tumour immune milieu optimal for targeting with immunotherapy.